2019
DOI: 10.1080/20550324.2019.1671038
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclay assisted ultra-drawing of polypropylene tapes

Abstract: Isotactic polypropylene (i-PP)montmorillonite (MMT) nanocomposite films were prepared by melt-compounding and hot-pressing. The influence of organoclays on the mechanical properties and drawability of these isotropic composite films was investigated. Ultimate properties of solid-state drawn PP tapes incorporating 2.5 wt% MMT outperformed those of pure PP tapes. Interestingly, these improvements were found not to be the result of a mechanical reinforcement effect of the nanoclay platelets but merely the result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Consequently, even higher values for the tensile strength are possible. Finally, it is worth mentioning that one of the highest tensile strength values, ever reported for PP composite drawn fibers, is 860 MPa and was achieved by the addition of montmorillonite and ultra-high drawing ratio equal to 27 [ 69 ], which, however, results in non-negligible shrinkage of fibers with aging.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, even higher values for the tensile strength are possible. Finally, it is worth mentioning that one of the highest tensile strength values, ever reported for PP composite drawn fibers, is 860 MPa and was achieved by the addition of montmorillonite and ultra-high drawing ratio equal to 27 [ 69 ], which, however, results in non-negligible shrinkage of fibers with aging.…”
Section: Resultsmentioning
confidence: 99%
“…25 However, for another MMT modification, it was reported that MMT acted not as a nucleation agent, but as a processing additive resulting in increased composite fiber drawability. 42…”
Section: Crystallinity In Pp Composites and Fibersmentioning
confidence: 99%
“…In this case, the mechanical properties improvement was attributed not to the PP reinforcement, but to the MMT acting as a processing additive that resulted in increased drawing ability. 42 Cloisite V R 20 A filler was also used to prepare PP nanocomposite fibers. SEM images showed that nanocomposite fibers presented more uniform surface, more narrow fiber diameter distribution and less roughness.…”
Section: Mineral Clay Composite Fibersmentioning
confidence: 99%
“…In other words, did the improvements in fibre properties come directly from the nanofiller or indirectly from a modification of the polymer matrix by the nanofiller, leading to higher draw ratios and improved mechanical properties? For example, while Wang et al [53], showed that mechanical property improvement in their oriented PVA/ SWCNT system was the direct result of effective nanotube reinforcement, property improvement in the oriented PP nanocomposite system of Van Erp et al [63] was merely the result of improved drawability. Another reason to doubt the effectiveness of nanofillers in fully chain extended polymer systems is related to their effect on the packing density of polymer chains.…”
Section: Introductionmentioning
confidence: 99%